Modification of an ignition quality tester and its use in characterizing middle distillate fuels - Ehrenreich, Aidan Lloyd (Department of Mechanical Engineering, 2015)
The Ignition Quality Tester ( IQTTM ) is a constant volume combustion chamber based device which is used to determine the derived cetane number of diesel fuel oils when used in conjunction with ASTM D6890. During a test, the fuel sample is injected into heated, pressurised gas where it combusts. Suitable measurements are made during the combustion event to determine the ignition delay of the fuel and the latter is used with a correlation to determine the derived cetane number of the sample. The IQT offers improved repeatability and reproducibility when compared with the conventional method of determining cetane number, namely ASTM D613. Despite these advantages, the device features a fuel injection system not indicative of the state of the art, in terms of direct injection diesel components and associated fuel spray behavior. Therefore this project sought to make suitable mechanical, electrical and control modifications to incorporate a more technologically appropriate injector. It is believed that by improving the spray characteristics of the IQT along with the incorporation of a flexible control system, that it can be leveraged to a greater extent in a fuels research context. The modifications made to the system included the incorporation of a single hole common rail diesel injector along with a custom control system. The control system allowed flexible control of all variables considered to be significant to the study of auto-ignition delays. Additionally, an optical sensor was added to detect luminous emissions from the reacting fuels. The modified system was used to rate diesel fuels with varied composition including solvents, diesel primary reference fuels, crude derived as well as Low Temperature Fischer Tropsch (LTFT) products. These tests were performed at two temperatures and oxygen concentrations and the resulting data was used to redevelop correlations between the cetane number of the respective samples and their ignition delays in order to surmise the optimal operating conditions of the modified IQT.